A covalent organic polymer as an efficient chemosensor for highly selective H2S detection through proton conduction. Issue 65 (16th July 2020) - Maiti, Sayan; Mandal, Biswajit; Sharma, Meenu; Mukherjee, Shaibal; Das, Apurba K.
Abstract : An interdigitated electrode fabricated with a covalent organic polymer (COP ) acts as an efficient H2 S gas sensor at room temperature. Abstract : A hydrazide based covalent organic polymer (COP ) with pyridine functionalities has been synthesized and used to fabricate an efficient chemosensor for the detection of gaseous H2 S at 25 °C through a proton conduction process. The gas sensing behavior of the COP has been measured in a dynamic flow-through resistance measurement system. The COP fabricated sensor shows a lower response time of 9 s with a recovery time of 12 s, when the experiment is performed with a H2 S concentration of 200 ppm at 25 °C. It also shows high selectivity to H2 S gas compared to other gases such as CO2, NH3, CO and NO2 .